Comparing High Definition Live Interactive and Store-and-Forward Consultations to In-Person Examinations - Marchell, Richard (Telemed J E Health, 2017)
Background: There is little teledermatology research directly comparing remote methods, even less research with two in-person dermatologist agreement providing a baseline for comparing remote methods, and no research using high definition video as a live interactive method. Objective: To compare in-person consultations with store-and-forward and live interactive methods, the latter having two levels of image quality. Methods: A controlled study was conducted where patients were examined in-person, by high definition video, and by store-and-forward methods. The order patients experienced methods and residents assigned methods rotated, although an attending always saw patients in-person. The type of high definition video employed, lower resolution compressed or higher resolution uncompressed, was alternated between clinics. Primary and differential diagnoses, biopsy recommendations, and diagnostic and biopsy confidence ratings were recorded. Results: Concordance and confidence were significantly better for in-person versus remote methods and biopsy recommendations were lower. Store-and-forward and higher resolution uncompressed video results were similar and better than those for lower resolution compressed video. Limitations: Dermatology residents took store-and-forward photos and their quality was likely superior to those normally taken in practice. There were variations in expertise between the attending and second and third year residents. Conclusion: The superiority of in-person consultations suggests the tendencies to order more biopsies or still see patients in-person are often justified in teledermatology and that high resolution uncompressed video can close the resolution gap between store-and-forward and live interactive methods.